Exploring the effects of International Students’ Acculturative Stress and Psychological Wellbeing: A Moderated Mediation Analysis - Thomas, Feba; Sumathi, G.N. (International Journal of Psychosocial Rehabilitation, 2020)
There is a dearth in the research in observing the moderation of social support in acculturation and acculturative stress among foreign students. The main purpose of the current study is to examine acculturative stress faced by the international students and the relationship of acculturation and acculturative stress among international students with the student outcome mental health.A cross-sectional research design was adopted. A total of 330 foreign students studying in Indian University (male=146, female=184) international students come from countries like Nepal, China, Rwanda, DR Congo, Cameroon, Somalia, Bangladesh, South Korea, Turkey, Zimbabwe, Uganda, Zambia, and Malaysia. The validity and reliability of the Scales are established. Structural equation modelling was conducted using Smart PLS 3.0 with 330 samples of foreign students.The results indicate that social support is a moderating variable that helps in the reduction of stress among international students to a greater extent. The theoretical and managerial implications are also discussed.This study will be blueprint for many institutions and the international companies to understand the acculturative strategies and the culture shock the individual possess when they are away from native country and come to a host country.The study has complimented the previous studies conducted on acculturative stress and it has given an insight on the moderated mediated relationship that exists with acculturation and acculturative stress when there is a student outcome mental health among international students.